The Household, Income and Labour Dynamics in Australia (HILDA) Survey: Wave 1 Survey Methodology - Wooden, M; Watson, N (Melbourne Institute of Applied Economic and Social Research, 2002)
This paper details the survey methodology employed for Wave 1 of the Household, Income and Labour Dynamics in Australia (HILDA) Survey. A brief description of the survey instruments is initially provided together with how these instruments were administered. Details of the sample design are then presented including a description of the reference population, sampling units and how the sample was selected. The subsequent sections detail the fieldwork procedures followed, the response rates obtained, and the data processing undertaken.
HILDA Project Technical Paper Series
Keywords: Surveys and Survey Methodology; Surveys and Survey Methodology -- Dataset cleaning and development; Surveys and Survey Methodology -- Fieldwork; Surveys and Survey Methodology -- Sample; Surveys and Survey Methodology; Surveys and survey methodology; Surveys and Survey Methodology; Sample; Fieldwork; Dataset cleaning and development; Surveys and Survey Methodology